ACUTE ANXIOLYTIC EFFECT OF AQUEOUS EXTRACT OF FRUITS OF TERMINALIA CHEBULA (AETC) IN MICE - CHANDRASHEKAR. R,; MANOHAR V.R,; RAO S.N, (International Journal of Pharma and Bio Sciences, 2012)
Anxiety is a psychological and physiological state characterized by cognitive, somatic, emotional, and behavioural components. Benzodiazepines (BZDs) are the major class of compounds used in anxiety and they remain the most commonly prescribed treatment for anxiety. In the present study, we have attempted to evaluate the acute anxiolytic activity of aqueous extract of fruits of Terminalia chebula (AETC) by Light and Dark Arena in Swiss albino mice. Mice weighing 25-30gm were divided into 5 groups containing 6 animals for each dose and were housed for 10 days prior to testing. The control (1% Gum acacia), test drug AETC (1.3, 2.6 and 5.2 mg/ kg) and standard drug Diazepam (1.0 mg/kg) were administered orally. One hour after oral administration of the drugs / vehicle, the experiment was conducted by Light and Dark Arena in Swiss albino mice. The results suggest that, behavioural disinhibitory effects of AETC exhibited anxiolytic activity at the dose of 1.3 and 2.6 mg/kg comparable to diazepam.